2017
DOI: 10.3748/wjg.v23.i18.3315
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive behavior in the workplace: Challenges for gastroenterology fellows

Abstract: AIMTo assess first-year gastroenterology fellows’ ability to address difficult interpersonal situations in the workplace using objective structured clinical examinations (OSCE).METHODSTwo OSCEs (“distracted care team” and “frazzled intern”) were created to assess response to disruptive behavior. In case 1, a fellow used a colonoscopy simulator while interacting with a standardized patient (SP), nurse, and attending physician all played by actors. The nurse and attending were instructed to display specific disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Another question becoming evident from the results is the factor of educating and teaching medical students about distraction in the medical field. Srisarajivakul et al tried to integrate the approach of disruptive behaviour into an OSCE station which can also be seen as a distracting agent [ 14 ]. Analysing the points achieved in the different domains of the checklist of the two OSCEs revealed that the students scored significantly less points in essential steps during the venous canulation and the abdominal pain station.…”
Section: Discussionmentioning
confidence: 99%
“…Another question becoming evident from the results is the factor of educating and teaching medical students about distraction in the medical field. Srisarajivakul et al tried to integrate the approach of disruptive behaviour into an OSCE station which can also be seen as a distracting agent [ 14 ]. Analysing the points achieved in the different domains of the checklist of the two OSCEs revealed that the students scored significantly less points in essential steps during the venous canulation and the abdominal pain station.…”
Section: Discussionmentioning
confidence: 99%